Generation Y Malaysian women perspectives towards solo traveling - Toh, Jen Ying (2017)
This thesis entitled “Generation Y Malaysian Women Perspectives towards Solo Travelling”. It is intended to focus on the perspectives of solo travelling from the Generation Y women in Malaysia. The emergence of women’s leisure in generation Y and the dynamic development on gender discourses mirrors the increase in tourism. Women solo traveller is not a new occurrence in the tourism yet in Southeast Asia, reviews about women solo travellers is relatively limited. This trend is a phenomenon to illustrate the differences of West and Asia perceptions and to identify social and cultural influences for them on decision to travel solo. It represents the motivations and the constraints of women’s solo travel to a country or destinations be it in a group, or being solo throughout the journey. The main objective is to understand the gen Y perspectives’ on solo travelling and how they make decisions to travel. Women’s leisure in Asia is drawing differentiation of cultural aspects which can influence in taking part in solo travel. Therefore, even solo travel is an emerging trend in Asia, yet the root culture in Asia is still retained and added more value in this type of travelling pattern. Basically, this study aims to identify the features of Malaysian women on participate in travel solo and the roles of Malaysian Women as a dominant gender discourses in individual’s cultures as a whole. This study used qualitative approach which sets out to explore Malaysian women in gen Y between 19-33 years old. They are the representative in this study particularly in solo travel. Sixteen in-depth interviews were held. The main focus was to allow the women to speak on their roles and experiences and identify their perceptions regard solo travelling. It reflects how gender can be links with leisure and the social and cultural attributes. The results reveal that social and cultural did not influences on their leisure but solo travelling can be influenced by personal identity or social identity. Three themes were identified throughout the findings which are travel motivation, social and cultural attributions, and the characteristics and planning approaches of gen Y. The findings of this study show that Asian women’s leisure is prevalent and women are able to have their own lives despites traditional ideologies, yet the result present the constraints of undertake solo travel as part the travel pattern is concerned. The main rationale is the safety of themselves as victim and also the security of destinations which make women’s travel vulnerable. Therefore, majority of Malaysian women prefer to travel in groups instead. In conclusion, this study has been conducted to assess the viewpoints of Malaysian women in gen Y where there is potential on growing market in gen Y and leisure these days. Tourism is a versatile and vibrant concept so the impacts of women’s leisure are vital factors for the policy makers, tourism marketers and any related business to comprehend the characteristics and the needs of women’s travellers especially in solo travelling. It also provides a dimension where West and Asia features is highlighted.